Lizards fail to plastically adjust nesting behavior or thermal tolerance as needed to buffer populations from climate warming. (9th September 2016) - Telemeco, Rory S.; Fletcher, Brooke; Levy, Ofir; Riley, Angela; Rodriguez‐Sanchez, Yesenia; Smith, Colton; Teague, Collin; Waters, Amanda; Angilletta, Michael J.; Buckley, Lauren B.
Abstract: Although observations suggest the potential for phenotypic plasticity to allow adaptive responses to climate change, few experiments have assessed that potential. Modeling suggests that Sceloporus tristichus lizards will need increased nest depth, shade cover, or embryonic thermal tolerance to avoid reproductive failure resulting from climate change. To test for such plasticity, we experimentally examined how maternal temperatures affect nesting behavior and embryonic thermal sensitivity. The temperature regime that females experienced while gravid did not affect nesting behavior, but warmer temperatures at the time of nesting reduced nest depth. Additionally, embryos from heat‐stressed mothers displayed increased sensitivity to high‐temperature exposure. Simulations suggest that critically low temperatures, rather than high temperatures, historically limit development of our study population. Thus, the plasticity needed to buffer this population has not been under selection. Plasticity will likely fail to compensate for ongoing climate change when such change results in novel stressors.